Description of the National Student Musabaqah Tilawatil Qur'an Competition 2023 Indonesian Education University Sumedang - Rahmah, Salsabila Saskia; Astutik, Anita Puji (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Musabaqah Tilawatil Quran (MTQ) is a competition event held to assess participants' ability to read, memorize and understand the Al-Quran. This competition has several categories, including Tilawah (recitation), Tajwid (application of reading rules). Participants from various levels compete to show their skills in reading and understanding the Koran according to established rules. The jury consisting of tajwid experts and ulama is responsible for assessing participants based on certain criteria. The MTQ competition is not just a competition, but also a means to strengthen spiritual connections with the Koran and increase understanding of Islamic teachings.